(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The present study was planned to investigate the possible association between polymorphisms of superoxide dismutase, SOD1 (Cu,Zn-SOD), SOD2(Mn-SOD), SOD3(EC-SOD) and catalase genes and the risk of cervical cancer in rural population of Maharashtra. Methods: A case control study included 350 proven cervical cancer cases and 400 healthy age matched control women. Genotyping of isoforms of SOD and CAT were done by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) method. Results: When we studied genotype frequencies of codon 326 and 262 region of promoter of CAT gene, there was no significant association between A to T transition at codon 326 (p=0.45) and CAT C262T polymorphism (p=0.30) with susceptibility to cervical cancer. The variant G allele of SOD1 at codon 251 significantly increased in cervical cancer patients as compared with the control women (OR=3.02, 95% CI: 1.72-5.31; p<0.0001). Conclusion: Findings from this investigation confirms conceivable association of A251G of SOD1 and G172A of SOD3 genes with risk of cervical cancer in women of Maharashtra.